Epidemiology of Some Parasitic Helminthes in Iraq from 2011 until 2015 - Saheb, Entsar J.; Mahdi , Sinan Ghazi; Mosa, Israa S.; Abdul Karim, Muthana Ibrahim; Khistawi, Adnan Nawar (Iraqi Journal of Science, 2022)
Helminthes are among transmitting pathogens including Ancylostomiasis,Ascariasis, Enterobiasis, Hymenolepiasis, Strongyloidiasis, Taeniasis, Trichuriasis,Schistosomiasis, Echinococcosis. These helminthes have high effect on publichealth in human population around the world. Iraq is one of the most importantendemic areas in the Middle East.The objective of this study is to determine theprevalence of some parasitic helminthes in Iraq from 2011 until 2015. This studywas carried out in all Iraqi governorates from 2011until June, 2015.In 2015, theresults showed that 6 patients were infected with Ancylostomiasis, 89 patients wereinfected with Ascariasis, 56206 patients were infected with Enterobiasis, 173patientswere infected with Hymenolepiasis, non-patient infected with Strongyloidiasis.25patients were infected with Taeniasis, 9 cases were infected with Trichuriasis.During the last five years, Iraq was absent of schistosomiasis. ConcedingEchinococcosis infection, there were a total of 4769 patients. In 2011, 2012 and2013 Najaf showed the highest incidence rates of infections 302 patients,277patients and 215 patients respectively, while Babel, Salaheldin, Wasit, Anbar andBaghdad kerkh governorates had the lowest rate of Echinococcosis infection. In2014, Thiqar showed the highest incidence rates of Echinococcosis infections (168patients).In 2015, 81 patients were found in Najaf which reveling the highestincidence rate. Baghdad kerkhdid not record any infections. In conclusion during thetime of this study, Iraq successfully eliminate Strongyloidiasis and schistosomiasis,on the other hand Enterobiasis and Echinococcosis represents a health problem inIraq.